Dynamics Of Job Quitting Among High Educated Female Former Employees - Aditya Utama, J. Seno (INTERNATIONAL RESEARCH JOURNAL OF BUSINESS STUDIES, 2012)
The number of highly educated woman workers increased in recent year, but job quitting and woman career discontinuity was still high; it was related to working inequalities and work-family issues. The current study investigates the antecedent of woman job quitting decision, career aspiration, spouse and supervisor support. Individual in-depth interviews investigated the 12 highly educated ex-employee mothers. The findings were spouse support on woman job quitting, children care orientation, supervisor retention effort, current positive evaluation and unintended future career.DOI :Â https://doi.org/10.21632/irjbs.5.2.101-112Keywords: job quitting,work-family,woman career